Quality of life during COVID-19 pandemic in Nepal: An online quantitative study. - Bista, Anu (2021)
ABSTRACT: Background: Several studies conducted on diseases outbreaks and quality of life (QoL) showed that people suffering from those diseases were found to have poor QOL than that of normal individual. COVID-19 has affected the globe and Nepal is not an exceptional. With high cases of COVID-19, Nepal initiated second phase national wide lockdown from April, which directly or indirectly impact on different dimension of QoL. Therefore, in this study, we aimed to assess QoL among general population amid COVID-19 context in Nepal and evaluate the effects of different sociodemographic factors that affects QoL. Methods: A cross-sectional online study was conducted among 824 respondents using google form during second wave of COVID-19 in Nepal. Socio-demographic data including age, sex, caste/ethnicity, income, job, marital status, location, use of alcohol, tobacco, self-history of COVID-19 and chronic diseases, family history of COVID-19 and chronic diseases were collected. QOL was assessed using World Health Organization Quality of Life (WHoQOL-BREF) questionnaire, where four domains (physical, psychological, social, and environmental) and two items (overall perception of QoL and health) were the outcome variable of this study. Independent t-test and one way analysis of variance (ANOVA) was used as part of bivariate analysis to assess relationship between socio-demographic factors and outcome variables. Multiple linear regression analysis was performed to determine the predicators of QoL. Findings: The following QOL scores (mean ± SD) for various domains were obtained: physical domain (24.16±6.86), psychological domain (40.61±11.42), social domain (97.65±28.92), and environmental domain (18.30±8.56). People infected with COVID-19, family history of COVID19, chronic disease family history and self-chronic diseases and tobacco use were the negative predicators of different domain of QOL during COVID-19 pandemic in Nepal. Likewise, respondents with jobs during survey and high monthly income found as positive predicators of QOL. Conclusion: Public health program planner and policy makers should focus on limiting the transmission of COVID-19 and develop prevention and early diagnosis and prompt treatment mechanism for treatment of chronic diseases as part of response mechanism to COVID-19 and routine primary care in Nepal.